The impact of new ambient air quality standards on green total factor energy efficiency: Evidence from an environmental information disclosure policy in China - Liu, Xing-Yuan; Wen, Hong-Xing; Ding, Duo-Dong (Frontiers in Environmental Science, 2023)
The implementation of the new ambient air quality standards (NAAQS) in 2012 is a milestone in China's environmental information disclosure process. The fully automated collection and publication of pollution information provides a convenient way to measure the environmental protection process around the country. This paper investigates the association between NAAQS and green total factor energy efficiency (GTFEE) enhancement in Chinese resource-based cities. Using the generalized multiperiod DID method and 2004-2019 panel data from 282 prefecture-level cities, we find that the implementation of this NAAQS significantly promotes GTFEE’s improvement in China’s resource-based cities. Furthermore, we discover that both the type of industrial base and the initial public monitoring motivation influence the improvement effect of the NAAQS on GTFEE. In further studies, NAAQS enhances GTFEE through industrial structure optimization, and the magnitude of the local NAAQS effect is influenced by the level of green innovation.